A qualitative study of the experiences of young people with severe mental health problems and complex needs regarding youth flexible assertive community treatment - Johansen, Marthe; Stuen, Hanne Kilen; Brekke, Eva; Jensen, Camilla Bergsve; Landheim, Anne (Frontiers in Psychiatry, 2024)
Youth Flexible Assertive Community Treatment (Youth Flexible ACT) is a service model for children and young people with severe mental health problems and complex needs aimed at providing integrated, continuous and holistic care. Studies on young people’s experiences of Youth Flexible ACT or similar models are scarce. The present qualitative study aimed to explore and describe how young people with severe mental health problems and complex needs experience follow-up and treatment provided by Youth Flexible ACT teams. Semi-structured interviews were conducted with 14 young people (age range, 15–19 years) who were being followed up by a Youth Flexible ACT team. Qualitative content analysis was used, and the following two overarching themes characterizing the young people’s experiences of follow-up and treatment provided by Youth Flexible ACT teams were identified: (1) trusting and collaborative relationships, and (2) organization matters. The participants experienced a more personal relationship with the staff, who behaved more like friends and paid attention to resources, interests, solutions and their context. The participants emphasized and valued components that coincided with the Youth Flexible ACT model, indicating a match between what the young people needed and wanted and what the model was supposed to provide. The team providing these relationships and youth-friendly and developmentally sensitive care appeared to be facilitated by how the service model was organized, with the teams being flexible and accessible while providing integrated, multifaceted help and systemic follow-up.